The Effect of Health Education with Spinning Wheel Game Method on the Khowledge of Sexual Education in SMPS Plus Karya Persada Muna - Muslifah; Arnia; Nur Juliana; Saputra, Erwin (Universitas Sulawesi Barat, 2022)
Adolescence is a time full of curiosity about everything, including sexual problems. At this time, adolescents need sexual education guidance for personal formation. The purpose of this study was to determine the effect of health education on the spinning wheel game method on knowledge of sexual education in students of SMPS Plus Karya Persada. This type of research uses a pre experimental design with pre and posttest methods without control. The sampling technique used probability sampling with random sampling involving 44 students in grades VII, VIII and IX. Data analysis used by non-parametric through wilcoxon test. The results showed that there was a difference in knowledge before and after being given sexual education with the spinning wheel method, the data showed that prior to the health education, the students' knowledge was in the category of poor (11,4%), sufficient (61,4%) and good (27,3%), while after using the spinning wheel method, the category increased to moderate (25,0%) and good to 75,0%). The average results obtained before and after being given education on the spinning wheel method were 69,18 and 81,98, respectively. The results of the analysis p-value 0,000 means p-value <0,05. Knowledge test results 0,000. This means that there is an effect of sexual education on the spinning wheel method on the knowledge of SMPS Plus Karya Persada Muna. Need the development of methods of spinning wheel so as to facilitate media android based learning to enhance students knowledge of sexual education.